2020
DOI: 10.3390/agronomy10101512
|View full text |Cite
|
Sign up to set email alerts
|

Melon Genetic Resources Characterization for Rind Volatile Profile

Abstract: A melon core collection was analyzed for rind volatile compounds as, despite the fact that they are scarcely studied, these compounds play an important role in consumer preferences. Gas chromatography coupled to mass spectrometry allowed the detection of 171 volatiles. The high volatile diversity found was analyzed by Hierarchical Cluster Analysis (HCA), giving rise to two major clusters of accessions. The first cluster included climacteric and aromatic types such as Cantalupensis, Ameri, Dudaim and Momordica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
4
10
1
Order By: Relevance
“…Melon fruit is distinguished by climacteric (reticulatus and cantaloupe type) and non-climacteric (inodorus type) characteristics [32,33]. is study used melon with climacteric character.…”
Section: Content Of Vitamin a Vitamin C And Tss At Five Maturity Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melon fruit is distinguished by climacteric (reticulatus and cantaloupe type) and non-climacteric (inodorus type) characteristics [32,33]. is study used melon with climacteric character.…”
Section: Content Of Vitamin a Vitamin C And Tss At Five Maturity Stagesmentioning
confidence: 99%
“…e hormone ethylene in climacteric melon causes this type of melon to be harvested when the fruit is not yet ripe. However, climacteric fruit harvested early causes fruit to be underripe [33], while fruit harvested late causes fruit to be too ripe when consumed [35]. e determination of the right harvest time is needed to maintain the quality of melons.…”
Section: Content Of Vitamin a Vitamin C And Tss At Five Maturity Stagesmentioning
confidence: 99%
“…The levels of esters detected in the Ibericus landraces were low, a characteristic typical of non-climacteric melons. Previous works have shown that Ibericus melons have levels of esters in the rind similar to Cantaloupensis climacteric melons, but the contents are considerably reduced in the flesh [54]. Indeed, when wide collections of melon germplasm have been analysed for their VOC profile, Inodorus melons, which include the Ibericus group, are grouped with sweet and non-sweet non-climacteric melons with low VOCs accumulation and non-sweet climacteric melons, such as Flexuosus, Chate, Ameri, and Momordica.…”
Section: Discussionmentioning
confidence: 92%
“…This special character comes from Hikapel's ancestor, namely the GMP (Gama Melon Parfum) cultivar. The aroma of melon has been identified as coming from volatile compounds dominated by acetic esters and non-acetic esters [19]. In certain conditions, the turbine which is the main character of the GMP cultivar still appears in the Hikapel cultivar, although in an exceedingly small percentage.…”
Section: A Identification Of Morphological Charactersmentioning
confidence: 99%